Window material and translucent roof material

By using an adhesive layer composed of temperature-sensitive adhesive and polymer particles in window materials or translucent roof materials, the problems of complex window structure and high manufacturing cost in the prior art are solved, and autonomously based on temperature Changing the white turbidity, simple structure and easy to manufacture, suitable for window materials and translucent roof materials.

CN119487279APending Publication Date: 2025-02-18NITTA CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380051101.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the window structure of the temperature-sensitive dimming liquid laminate is complex and has high manufacturing cost, and there is a problem of manufacturing time.

Method used

A window material or a translucent roof material including at least one layer of light-transmitting substrate and one layer of adhesive layer is adopted. The adhesive layer is composed of a thermosensitive adhesive and polymer particles, and the thermosensitive adhesive is bonded. The refractive index of the agent increases with the decrease in temperature, and the adhesion force decreases with the decrease in temperature.

Benefits of technology

It realizes the white turbidity independently changing according to the temperature, the structure is simple and easy to manufacture, and is suitable for window materials and translucent roof materials. It can relieve direct sunlight at high temperatures in summer and receive sunlight at low temperatures in winter.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487279A_ABST
    Figure CN119487279A_ABST
Patent Text Reader

Abstract

Provided are: a window material or a light-transmitting roof material which can autonomously change white turbidity in accordance with temperature, has an uncomplicated structure, and is easy to manufacture; a building provided with the window material and / or the light-transmitting roof material; and a vehicle, a ship, or an aircraft. This window material or light-transmitting roof material is provided with at least one light-transmitting substrate layer and at least one adhesive layer, the adhesive layer comprising an adhesive composition containing 1-100 parts by mass of polymer microparticles per 100 parts by mass of a temperature-sensitive adhesive, and the refractive index of the temperature-sensitive adhesive increases as the temperature decreases. The refractive index increase rate near the melting point of the thermo-sensitive adhesive is greater than a temperature region other than the melting point, the adhesive force of the adhesive composition decreases as the temperature decreases, and the adhesive force decrease rate near the melting point of the thermo-sensitive adhesive is greater than a temperature region other than the melting point.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a window material and a light-transmitting roof material and also to a building, a vehicle, a ship or an aircraft equipped with the window material and / or the light-transmitting roof material. Background Art

[0002] In buildings such as office buildings and arcades, or in vehicles such as vehicles, ships, and aircraft, there is a need to mitigate direct sunlight during high temperatures in summer and to take in sunlight during low temperatures in winter. In response to this, a temperature-sensitive dimming liquid laminate whose white turbidity changes autonomously in response to temperature stimulation has been proposed as a structure to be installed in a window (Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 3337810 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] In order to provide the above-mentioned stacked body, a dedicated structure for maintaining the shape of the temperature-sensitive light-adjusting liquid is required, and there is a problem that the structure of the window provided with the above-mentioned stacked body becomes complicated, and the manufacturing process is labor-intensive.

[0008] The present invention has been completed in view of the above-mentioned problems, and its purpose is to provide a window material or a translucent roof material that can autonomously change the white turbidity according to the temperature, has a simple structure and is easy to manufacture, a building having the window material and / or the translucent roof material, and a vehicle, a ship or an aircraft.

[0009] Solutions for solving problems

[0010] A first aspect of the present invention is a window material, wherein:

[0011] It comprises at least one light-transmitting substrate layer and at least one adhesive layer,

[0012] The adhesive layer includes an adhesive composition containing 1 to 100 parts by mass of polymer microparticles relative to 100 parts by mass of the temperature-sensitive adhesive.

[0013] The refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and

[0014] The increase in refractive index per 1°C, that is, the rate of increase in refractive index of the temperature-sensitive adhesive, is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

[0015] The adhesive force of the adhesive composition decreases as the temperature decreases, and

[0016] The amount of decrease in adhesive strength per 1° C., that is, the adhesive strength reduction rate of the adhesive composition is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

[0017] A second aspect of the present invention is a light-transmitting roof material, wherein:

[0018] It comprises at least one light-transmitting substrate layer and at least one adhesive layer,

[0019] The adhesive layer includes an adhesive composition containing 1 to 100 parts by mass of polymer microparticles relative to 100 parts by mass of the temperature-sensitive adhesive.

[0020] The refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and

[0021] The increase in refractive index per 1°C, that is, the rate of increase in refractive index of the temperature-sensitive adhesive, is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

[0022] The adhesive force of the adhesive composition decreases as the temperature decreases, and

[0023] The amount of decrease in adhesive strength per 1° C., that is, the adhesive strength reduction rate of the adhesive composition is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

[0024] A third aspect of the present invention is a building comprising the window material according to the first aspect and / or the light-transmitting roofing material according to the second aspect.

[0025] A fourth aspect of the present invention is a vehicle, a ship, or an aircraft, comprising the window material according to the first aspect and / or the light-transmitting roof material according to the second aspect.

[0026] A fifth aspect of the present invention is an adhesive composition comprising 1 to 100 parts by mass of polymer fine particles per 100 parts by mass of the temperature-sensitive adhesive, wherein:

[0027] The refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and

[0028] The increase in refractive index per 1°C, that is, the rate of increase in refractive index of the temperature-sensitive adhesive, is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

[0029] The adhesive force of the adhesive composition decreases as the temperature decreases, and

[0030] The amount of decrease in adhesive strength per 1° C., that is, the adhesive strength reduction rate of the adhesive composition is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

[0031] A sixth aspect of the present invention is a pressure-sensitive adhesive sheet, wherein:

[0032] A pressure-sensitive adhesive layer comprising the pressure-sensitive adhesive composition according to the fifth aspect is provided.

[0033] A seventh aspect of the present invention is a method for processing a workpiece, wherein:

[0034] Include:

[0035] bringing a workpiece into contact with the adhesive layer of the adhesive sheet according to the sixth aspect;

[0036] Confirming that the adhesive layer exhibits adhesive strength by confirming that the adhesive layer becomes cloudy or does not become cloudy;

[0037] processing the workpiece fixed to the adhesive layer by the adhesive force exerted by the adhesive layer;

[0038] Confirming that the adhesive layer does not exhibit adhesive force by confirming that the adhesive layer is not cloudy or is cloudy; and

[0039] The processed object is removed from the adhesive layer which does not exhibit adhesive force.

[0040] An eighth aspect of the present invention is a method for processing a workpiece, wherein:

[0041] Include:

[0042] bringing a support body and a workpiece, or bringing the workpieces into contact with each other via the adhesive layer provided in the adhesive sheet according to the sixth aspect;

[0043] Confirming that the adhesive layer exhibits adhesive strength by confirming that the adhesive layer becomes cloudy or does not become cloudy;

[0044] Processing the object fixed to the support through the adhesive layer by the adhesive force of the adhesive layer, or at least one of the plurality of objects fixed through the adhesive layer;

[0045] Confirming that the adhesive layer does not exhibit adhesive force by confirming that the adhesive layer is not cloudy or is cloudy; and

[0046] The processed object is removed from the adhesive layer which does not exhibit adhesive force.

[0047] Effects of the Invention

[0048] According to the present invention, there can be provided a window material or a light-transmitting roof material which can autonomously change the white turbidity according to the temperature, has a simple structure and is easy to manufacture, and a building, a vehicle, a ship or an aircraft having the window material and / or the light-transmitting roof material. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 : is a cross-sectional view showing a first window material as an example of a window material.

[0050] Figure 2 : is a cross-sectional view showing a second window material as an example of a window material.

[0051] Figure 3 This is a cross-sectional view showing an example of a light-transmitting roofing material.

[0052] Figure 4 This is a graph showing the measurement results of the refractive index of the temperature-sensitive adhesive produced in Examples.

[0053] Figure 5 It is a schematic explanatory diagram showing the evaluation test method of the heat insulation in the examples.

[0054] Figure 6 The photographs show the evaluation test method of the heat insulation in the examples.

[0055] Figure 7 The photographs show the evaluation test method of the heat insulation properties in the examples. DETAILED DESCRIPTION

[0056] The specific embodiments of the present invention are described in detail below, but the present invention is not limited by the following embodiments and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, the following figures are schematically shown, and the size and shape of each part are appropriately exaggerated or omitted for easy understanding.

[0057] <<Window materials>>

[0058] exist Figure 1 , a cross-sectional view of a first window material 10 is shown as an example of a window material. Figure 1 As shown, in the first window material 10, a light-transmitting base material layer 11, an adhesive layer 12, and a base sheet 13 are laminated in this order. The adhesive layer 12 is composed of an adhesive composition containing a temperature-sensitive adhesive 12a and polymer microparticles 12b.

[0059] exist Figure 2 , as another example of a window material, a cross-sectional view of a second window material 20 is shown. Figure 2 As shown in FIG. 1 , in the second window material 20 , an adhesive layer 22 is disposed between two light-transmitting substrate layers 21 a and 21 b. The adhesive layer 22 is composed of an adhesive composition including a temperature-sensitive adhesive 22 a and polymer microparticles 22 b.

[0060] exist Figure 1 and Figure 2 In the embodiment, the refractive index of the temperature-sensitive adhesive 12a and 22a increases as the temperature decreases, and the increase in the refractive index per 1°C, i.e., the refractive index increase rate, is greater near the melting point than in the temperature range other than the melting point. Therefore, when the temperature of the adhesive layer 12 and 22 increases due to sunlight or air temperature, the refractive index difference between the temperature-sensitive adhesive 12a and 22a and the polymer particles 12b and 22b becomes larger, and the haze value becomes higher. On the other hand, when the temperature of the adhesive layer 12 and 22 decreases, the refractive index difference between the temperature-sensitive adhesive 12a and 22a and the polymer particles 12b and 22b becomes smaller, and the haze value becomes lower. Thus, the white turbidity can be changed autonomously according to the temperature, and direct sunlight can be mitigated at high temperatures in summer and sunlight can be taken in at low temperatures in winter.

[0061] Furthermore, it is also possible to design the structure so that the difference in refractive index between the temperature-sensitive adhesives 12 a and 22 a and the polymer microparticles 12 b and 22 b decreases as the temperature increases.

[0062] In this case, for example, in conditions where the temperature is relatively low and the amount of sunlight is small, such as in the morning or at night, the window material functions as frosted glass. On the other hand, during the day, when the temperature rises as the amount of sunlight increases, the window material becomes transparent and can efficiently let light into the room.

[0063] In addition, when the above-mentioned window material is constructed to a position in contact with the outside air, the above-mentioned window material becomes cloudy or transparent as the temperature of the outside air rises, and therefore also has the function of allowing people living in an air-conditioned room to visually recognize the increase in the temperature of the outside air.

[0064] Moreover, the adhesive force of the adhesive composition constituting the adhesive layers 12 and 22 decreases as the temperature decreases, and the amount of adhesive force reduction per 1°C, i.e., the adhesive force reduction rate, is greater near the melting point of the temperature-sensitive adhesive 12a and 22a in the adhesive composition than in a temperature range other than the melting point. Therefore, even if air bubbles are drawn in or wrinkles occur when configuring the adhesive layers 12 and 22, the adhesive layers 12 and 22 can be peeled off and configured again by lowering the temperature of the adhesive layers 12 and 22. Thus, the manufacture of the window material can be made easier.

[0065] Hereinafter, each layer constituting the first window material 10 and the second window material 20 will be described.

[0066] [Light-transmitting base material layer]

[0067] As the light-transmitting substrate constituting the light-transmitting substrate layer, as long as it can be used as a substrate for building, vehicle, ship, or aircraft window material, it is not particularly limited, and for example, a glass plate or a resin plate can be used. As the material of the glass plate, soda-lime glass, borosilicate glass, high silica glass, etc. can be cited. In addition, as the material of the resin plate, polymethacrylate alkyl esters such as polymethyl methacrylate, polyacrylate alkyl esters, polycarbonate, polymethyl styrene, acrylonitrile-styrene copolymers, etc. can be cited.

[0068] The thickness of the light-transmitting base material layer is not particularly limited, and is, for example, 0.1 mm to 10 mm. Examples of the shape of the light-transmitting base material layer include a flat surface shape such as the first window material 10 and the second window material 20 , and a curved surface shape.

[0069] The light-transmitting substrate layer is composed of at least one layer, and may be composed of a single layer as in the first window material 10, or may be composed of two or more layers as in the second window material 20. When composed of two or more layers, each layer may be composed of the same type of substrate, or may be composed of different types of substrates. In addition, each layer may be of the same thickness, or may be of different thicknesses.

[0070] [Adhesive layer]

[0071] The adhesive layer is a layer comprising an adhesive composition containing 1 to 100 parts by mass of polymer fine particles per 100 parts by mass of the temperature-sensitive adhesive, and has a function of autonomously changing white turbidity and adhesive strength according to temperature.

[0072] The thickness of the adhesive layer is not particularly limited, but is preferably 5 μm or more and 1 mm or less, and more preferably 10 μm or more and 100 μm or less. In addition, the thicker the adhesive layer, the more likely it is that a dimming function will be exhibited by adding a small amount of polymer particles. The thinner the thickness, the more likely it is that a large amount of polymer particles need to be added to exhibit the dimming function.

[0073] The adhesive layer is composed of at least one layer. The adhesive layer may be composed of a single layer as in the first window material 10 and the second window material 20, or may be composed of two or more layers. The configuration of the adhesive layer relative to the light-transmitting substrate layer is not particularly limited. The adhesive layer may be configured on the side where sunlight is incident relative to the light-transmitting substrate layer, or may be configured on the opposite side thereof. In the case where the light-transmitting substrate layer is composed of two or more layers, the adhesive layer may be configured between the light-transmitting substrate layers as in the second window material 20.

[0074] Furthermore, the adhesive layer may cover the entire surface of the surface in contact with the light-transmitting base layer, or may cover a portion of it.

[0075] In the case where the adhesive layer covers a part of the surface where the adhesive layer and the light-transmitting substrate layer are in contact, text, marks, patterns, graphics, designs, etc. can also be drawn on the light-transmitting substrate layer through the adhesive layer. In this case, the text or pattern can be formed by the adhesive layer, or the text or pattern can be formed in the area surrounded by the adhesive layer. Such a window material has excellent appearance design when the haze appears or disappears at high temperature.

[0076] Furthermore, the adhesive layer may have a plurality of regions having different haze values ​​at high temperatures or low temperatures. The haze value of the adhesive layer can be changed by changing the type of the temperature-sensitive adhesive or polymer microparticles or by changing the amount of polymer microparticles used.

[0077] For example, by continuously forming a plurality of adhesive layers having different haze values ​​at high or low temperatures in a strip shape on a light-transmitting substrate, a window material having excellent design properties showing a gradated haze at high or low temperatures can be provided.

[0078] The difference between the haze value of the adhesive layer at 23°C and the haze value at 60°C is preferably 10% or more. In particular, it is more preferred that the haze value of the adhesive layer at 60°C is 10% or more higher than the haze value at 23°C. Thus, there is a tendency that the change in white turbidity corresponding to temperature is easily visually recognized. In this specification, the haze value of the adhesive layer is a value measured by the method described in the examples described later.

[0079] The haze value of the adhesive layer at 23°C is preferably 20% or less, more preferably 10% or less. The lower limit of the haze value at 23°C is not particularly limited. In addition, the haze value of the adhesive layer at 60°C is preferably 12% or more, more preferably 20% or more. The upper limit of the haze value at 60°C is not particularly limited, for example, 70% or less, 50% or less.

[0080] The difference between the solar transmittance at 23°C and the solar transmittance at 60°C of the adhesive layer is preferably 10% or more. The solar transmittance at 60°C of the adhesive layer is preferably 10% or more lower than the solar transmittance at 23°C. In addition, in this specification, the solar transmittance of the adhesive layer is a value measured by the method described in the Examples described later.

[0081] The solar transmittance of the adhesive layer at 23°C is preferably 30% or more, more preferably 40% or more. The upper limit of the solar transmittance at 23°C is not particularly limited, and is, for example, 95% or less or 85% or less. In addition, the solar transmittance of the adhesive layer at 60°C is preferably 60% or less, more preferably 40% or less, and further preferably 30% or less. The lower limit of the solar transmittance at 60°C is not particularly limited, and is, for example, 5% or more or 15% or more.

[0082] (Polymer Microparticles)

[0083] The average particle size of the polymer particles is preferably 0.1 μm or more, more preferably 1 μm or more. In addition, the above average particle size is preferably 100 μm or less, more preferably 30 μm or less, and further preferably 10 μm or less. In particular, from the perspective of facilitating the improvement of haze, the above average particle size is further preferably 0.1 μm or more and 10 μm or less, and most preferably 1 μm or more and 6 μm or less. From the perspective of facilitating the transmission of sunlight, the above average particle size is further preferably 6 μm or more and 25 μm or less, and most preferably 6 μm or more and 10 μm or less. From the perspective of facilitating heat insulation, the above average particle size is further preferably 6 μm or more and 25 μm or less, and most preferably 6 μm or more and 10 μm or less.

[0084] In addition, the D90 particle size of the polymer particles is preferably less than the thickness of the adhesive layer, for example, from 1 μm to 1000 μm, from 3 μm to 100 μm. When the D90 particle size is less than the thickness of the adhesive layer, the surface of the adhesive layer becomes uniform, and there is a tendency that the adhesive force is not easily hindered. In addition, in this specification, the average particle size of the polymer particles is a value measured by the method described in the examples described later.

[0085] The polymer constituting the polymer microparticles preferably contains a constituent unit derived from a monomer containing one ethylenically unsaturated group. Examples of the ethylenically unsaturated group include (meth)acryloyl, (meth)acrylamide, vinyl and (meth)allyl groups, with (meth)acryloyl and vinyl groups being preferred.

[0086] Examples of the monomer containing one ethylenically unsaturated group include (meth)acrylic acid; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, and hydroxyethyl (meth)acrylate; vinyl monomers such as styrene, vinyl acetate, and acrylonitrile; etc. These may be used alone or in combination of two or more.

[0087] The ratio of the mass of the constituent units derived from the monomer containing one ethylenically unsaturated group to the mass of the polymer constituting the polymer microparticles is preferably 70 mass % or more, more preferably 80 mass % or more, and further preferably 90 mass % or more. The above ratio may be 100 mass %, but is preferably 98 mass % or less.

[0088] The polymer constituting the polymer microparticles may also contain constituent units derived from other monomers copolymerizable with the monomer containing one ethylenically unsaturated group. Examples of other monomers include multifunctional monomers, refractive index adjusting monomers, etc. That is, the polymer constituting the polymer microparticles may also contain constituent units derived from multifunctional monomers or refractive index adjusting monomers.

[0089] The multifunctional monomer can crosslink the multiple molecular chains contained in the polymer constituting the polymer particles. From the viewpoint of the dispersion state of the polymer particles during use or the suppression of deformation and the repeatability of the function, the polymer constituting the polymer particles preferably contains a constituent unit derived from the multifunctional monomer. That is, it is preferred that the polymer particles or the polymer constituting them are crosslinked. The multifunctional monomer has two or more, preferably 2 to 4, double bonds that can be free radically polymerized in the molecule. As multifunctional monomers, for example, bifunctional (meth) acrylates, trifunctional (meth) acrylates, and tetrafunctional (meth) acrylates can be cited. As specific examples, 1,6-hexanediol di(meth) acrylate, 1,9-nonanediol di(meth) acrylate, trimethylolpropane tri(meth) acrylate, pentaerythritol tetra(meth) acrylate, polyethylene glycol 200 di(meth) acrylate, ethoxylated bisphenol A di(meth) acrylate, etc. can be cited. They can be used alone or in combination of two or more. The polyfunctional monomer may be at least one selected from bifunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional (meth)acrylates.

[0090] The ratio of the mass of the constituent units derived from the polyfunctional monomer to the mass of the polymer constituting the polymer microparticles is preferably 0.1 mass % or more, more preferably 1 mass % or more, and preferably 20 mass % or less, more preferably 10 mass % or less.

[0091] The refractive index adjusting monomer may be a monomer having a refractive index of 1.300 to 1.600. Examples of the refractive index adjusting monomer include 2-(o-phenylphenoxy)ethyl acrylate (refractive index: 1.577), 2-(3-phenoxyphenyl)methyl acrylate (refractive index: 1.566), 1-naphthyl acrylate (refractive index: 1.595), acrylamide (refractive index: 1.515), hydroxyacrylamide (refractive index: 1.515), EO-modified bisphenol A diacrylate (refractive index: 1.537), acrylamide (refractive index: 1.515), 2,2,2-trifluoroethyl acrylate (refractive index: 1.348), and methacrylic acid-modified polydimethylsiloxane (refractive index: 1.408). These monomers may be used alone or in combination of two or more.

[0092] The ratio of the mass of the constituent units derived from the refractive index adjusting monomer to the mass of the polymer constituting the polymer microparticles is preferably 0.1 mass % or more, more preferably 1 mass % or more, and preferably 30 mass % or less, more preferably 20 mass % or less, and further preferably 10 mass % or less.

[0093] From the aspect of having a good dispersibility to the thermosensitive adhesive, the polymer microparticles preferably do not contain a constituent unit derived from a reactive emulsifier. A reactive emulsifier refers to an emulsifier having a polymerizable unsaturated bond such as a vinyl group in the molecule. A reactive emulsifier is a polymerizable monomer having an emulsifying function and having a hydrophilic group and a polymerizable group having an unsaturated bond such as a vinyl group in its molecule.

[0094] In the adhesive composition, the content of the polymer particles is 1 part by mass or more and 100 parts by mass or less relative to 100 parts by mass of the temperature-sensitive adhesive. The above content is preferably 5 parts by mass or more, more preferably 20 parts by mass or more. In addition, the above content is preferably 70 parts by mass or less, more preferably 40 parts by mass or less.

[0095] The method for producing polymer microparticles is not particularly limited, and the microparticles can be obtained by conventionally known polymerization methods such as mini-emulsion polymerization and suspension polymerization.

[0096] (Thermosensitive adhesive)

[0097] Thermosensitive adhesives have a melting point. Thermosensitive adhesives crystallize at a temperature lower than the melting point, and undergo a phase change and exhibit fluidity at a temperature above the melting point. As a result, the adhesive force of the adhesive composition containing the thermosensitive adhesive decreases as the temperature decreases, and the amount of decrease in adhesive force per 1°C, i.e., the adhesive force reduction rate, is greater near the melting point of the thermosensitive adhesive in the adhesive composition than in a temperature range other than near the melting point. In addition, in this specification, the adhesive force of the adhesive composition refers to the peel strength relative to polyethylene terephthalate (PET), which is a value measured by the method described in the examples described later.

[0098] The peel strength of the adhesive composition with respect to polyethylene terephthalate (PET) at 23° C. is preferably 0.1 N / 25 mm or less. The lower limit of the peel strength is not particularly limited.

[0099] The adhesive composition preferably has a peel strength of 1.0 N / 25 mm or more with respect to polyethylene terephthalate (PET) at 60° C. The upper limit of the peel strength is not particularly limited.

[0100] The melting point of the temperature-sensitive adhesive is preferably 25° C. or higher, more preferably 40° C. or higher. Also, the melting point is preferably 70° C. or lower, more preferably 60° C. or lower. In this specification, the melting point of the temperature-sensitive adhesive is a value measured by the method described in Examples below.

[0101] The melting point of the temperature-sensitive adhesive can be adjusted by, for example, changing the composition of the monomer components of the side chain crystalline polymer contained in the temperature-sensitive adhesive. For example, if the length of the side chain in the side chain crystalline polymer is changed, the melting point can be adjusted. When the length of the side chain is long, the melting point of the temperature-sensitive adhesive tends to be high.

[0102] Figure 4 Graph showing the change in refractive index of a temperature-sensitive adhesive (melting point 55° C.) produced in the examples described below with respect to temperature changes. Figure 4 As shown, the refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and the increase in refractive index per 1°C, i.e., the refractive index increase rate, is greater near the melting point than in a temperature range other than the melting point. In this specification, the refractive index is a value measured by the method described in the Examples below.

[0103] The refractive index of the temperature-sensitive adhesive at 23° C. is preferably 0.02 or more higher than the refractive index of the temperature-sensitive adhesive at 60° C. This tends to make it easier to visually recognize changes in white turbidity depending on temperature.

[0104] The temperature-sensitive adhesive preferably includes a side chain crystalline polymer. The side chain crystalline polymer preferably includes a constituent unit of a (meth) acrylic monomer having a straight-chain alkyl group with a carbon number of more than 14. In the constituent unit of a (meth) acrylic monomer having a straight-chain alkyl group with a carbon number of more than 14, the straight-chain alkyl group with a carbon number of more than 14 functions as a side chain crystalline site in the side chain crystalline polymer. That is, the side chain crystalline polymer is, for example, a comb-shaped polymer having a straight-chain alkyl group with a carbon number of more than 14 in the side chain. The side chain is integrated into an orderly arrangement by intermolecular forces, etc., so that the side chain crystalline polymer is crystallized. In addition, the above-mentioned (meth) acrylic monomer refers to an acrylic monomer or a methacrylic monomer. The upper limit of the carbon number of the straight-chain alkyl group is preferably less than 50, more preferably less than 30.

[0105] Examples of the (meth)acrylic acid monomer having a linear alkyl group having 14 or more carbon atoms include hexadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, and behenyl (meth)acrylate. These monomers may be used alone or in combination of two or more.

[0106] The ratio of the mass of the constituent units derived from the (meth)acrylic acid monomer having a linear alkyl group having 14 or more carbon atoms to the mass of the side chain crystalline polymer is preferably 30% by mass or more, more preferably 40% by mass or more. The above ratio is preferably 90% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less.

[0107] The side chain crystalline polymer preferably includes a constituent unit derived from a (meth) acrylic monomer having a linear alkyl group having a carbon number of 1 or more and 12 or less, and a constituent unit derived from a functional group monomer for crosslinking. In addition, the side chain crystalline polymer may also include a constituent unit derived from other monomers that can copolymerize with these monomers. As other monomers, for example, a refractive index adjusting monomer may be cited. That is, the side chain crystalline polymer may also include a constituent unit derived from a refractive index adjusting monomer.

[0108] As the (meth)acrylic acid monomer having a linear alkyl group with a carbon number of 1 to 12, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, etc. can be mentioned. Only one of them can be used, or two or more of them can be used in combination. Among them, methyl (meth)acrylate is preferred because it has high cohesive force and is easy to suppress the decrease in adhesive force when the temperature rises.

[0109] The ratio of the mass of the constituent units derived from the (meth)acrylic acid monomer having a linear alkyl group having 1 to 12 carbon atoms to the mass of the side chain crystalline polymer is preferably 1% by mass or more, more preferably 20% by mass or more, and further preferably 40% by mass or more. The above ratio is preferably 69% by mass or less, and more preferably 60% by mass or less.

[0110] Examples of the functional group monomer include (meth)acrylates having a hydroxyalkyl group such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxyhexyl (meth)acrylate; ethylenically unsaturated monomers having a carboxyl group such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid, and fumaric acid; etc. These may be used alone or in combination of two or more.

[0111] The mass of the constituent units derived from the functional group monomer relative to the mass of the side chain crystalline polymer is preferably 1% by mass or more, more preferably 3% by mass or more. In addition, the above ratio is preferably 20% by mass or less, more preferably 10% by mass or less. When it is 1% by mass or more, there is a trend that the shape retention is good. When it is 20% by mass or less, there is a trend that the viscosity does not excessively become high and the coating property is good.

[0112] The refractive index adjusting monomer may be a monomer having a refractive index of 1.300 to 1.600. Examples of the refractive index adjusting monomer include 2-(o-phenylphenoxy)ethyl acrylate (refractive index: 1.577), 2-(3-phenoxyphenyl)methyl acrylate (refractive index: 1.566), 1-naphthyl acrylate (refractive index: 1.595), acrylamide (refractive index: 1.515), hydroxyacrylamide (refractive index: 1.515), EO-modified bisphenol A diacrylate (refractive index: 1.537), acrylamide (refractive index: 1.515), 2,2,2-trifluoroethyl acrylate (refractive index: 1.348), and methacrylic acid-modified polydimethylsiloxane (refractive index: 1.408). These monomers may be used alone or in combination of two or more.

[0113] The ratio of the mass of the structural unit derived from the refractive index adjusting monomer to the mass of the side chain crystalline polymer is preferably 0.1 mass % or more, more preferably 1 mass % or more, and further preferably 10 mass % or more. The above ratio is preferably 30 mass % or less.

[0114] The weight average molecular weight of the temperature-sensitive adhesive is preferably 200,000 or more, more preferably 400,000 or more. The above weight average molecular weight is preferably 2,000,000 or less, more preferably 1,000,000 or less. When it is 200,000 or more, there is a tendency that the adhesive force is sufficient. When it is 2,000,000 or less, there is a tendency that the coating property is sufficient due to the reduction in viscosity. In addition, in this specification, the weight average molecular weight of the temperature-sensitive adhesive is a value measured by the method described in the examples described later.

[0115] The weight average molecular weight of the temperature-sensitive adhesive can be adjusted by, for example, using a chain transfer agent during polymerization. As the chain transfer agent, for example, mercaptan compounds such as dodecyl mercaptan, mercaptopropionic acid, mercaptosuccinic acid, ethylhexyl mercaptoacetate, mercaptoethanol, and cyclohexanethiol can be cited. These can be used alone or in combination of two or more.

[0116] The refractive index difference between the temperature-sensitive binder and the polymer microparticles at 23°C is preferably less than 0.015, more preferably less than 0.010. The refractive index difference at 60°C is preferably 0.015 or more. The upper limit of the refractive index difference at 60°C is not particularly limited, and is, for example, 0.1.

[0117] Thus, in general, in a warm atmosphere where people and pets can live comfortably, the adhesive layer exhibits high light transmittance, whereas in a high temperature atmosphere such as in summer, the light transmittance of the adhesive layer decreases due to the appearance of haze.

[0118] Alternatively, the refractive index of the temperature-sensitive adhesive and the polymer microparticles may be adjusted so that the difference in refractive index between the temperature-sensitive adhesive and the polymer microparticles at 23° C. is 0.015 or more and the difference in refractive index at 60° C. is less than 0.015.

[0119] In this case, for example, when the adhesive layer is applied to window glass, the window glass functions as frosted glass in conditions such as morning or night when the temperature is relatively low and the amount of sunlight is small, and on the other hand, when the temperature rises as the amount of sunlight increases during the day, the window material becomes transparent and can efficiently let in light into the room. In this way, even without opening or closing the curtain, it is easy to let in light into the room only during the day.

[0120] The ratio of the mass of the temperature-sensitive adhesive to the mass of the solid content of the adhesive composition is not particularly limited, and is, for example, 50% by mass or more and 95% by mass or less. In addition, in this specification, the solid content of the adhesive composition refers to all components after removing solvents such as aqueous solvents or organic solvents from the adhesive composition.

[0121] The method for producing the temperature-sensitive adhesive is not particularly limited, and the temperature-sensitive adhesive can be obtained by a conventionally known polymerization method such as solution polymerization and UV polymerization.

[0122] The adhesive composition may also contain a crosslinking agent for crosslinking the temperature-sensitive adhesive. That is, the temperature-sensitive adhesive may be crosslinked. Examples of the crosslinking agent include aziridine-based crosslinking agents, metal chelate-based crosslinking agents, epoxy-based crosslinking agents, and isocyanate-based crosslinking agents.

[0123] In the adhesive composition, the content of the crosslinking agent is not particularly limited, for example, relative to 100 parts by mass of the temperature-sensitive adhesive, it is 0.1 parts by mass or more and 10 parts by mass or less. When it is 0.1 parts by mass or more, there is a tendency that the shape retention is not easy to become low. In addition, when it is 10 parts by mass or less, there is a tendency that it is easy to exert high adhesive force.

[0124] The adhesive composition may contain other additives such as organic solvents, inhibitors for inhibiting the progress of crosslinking, tackifying resins (tackifiers), ultraviolet (UV) absorbers, light stabilizers (HALS), antioxidants, infrared absorbers, dyes, pigments, etc.

[0125] [use]

[0126] There is no limitation on the mode in which the above-mentioned adhesive composition is used. The mode in which the above-mentioned adhesive composition is used can be appropriately selected according to the purpose.

[0127] The above-mentioned adhesive composition can autonomously change the degree of white turbidity according to the temperature.

[0128] When the adhesive composition is designed so as to develop haze at high temperatures, it can mitigate direct sunlight in the high temperatures of summer and take in sunlight in the low temperatures of winter. Therefore, it can be suitably used, for example, in window materials and translucent roof materials.

[0129] On the other hand, when the adhesive composition is designed to show haze at low temperatures, for example, when the adhesive composition is applied to window glass, the window glass functions as frosted glass under conditions such as morning or night when the temperature is relatively low and the amount of sunlight is small. On the other hand, during the day, when the temperature rises due to an increase in sunlight, the window glass becomes transparent and can efficiently let in light into the room.

[0130] In addition, when the haze of the adhesive composition appears or disappears at high temperatures caused by heat sources such as lighting or sunlight or air temperature, it can make the appearance of words, marks, patterns, graphics, designs, etc. appear or disappear, and can give excellent display properties (appearance designs such as words and marks) or decorative properties (appearance designs such as patterns, graphics, designs, etc.) to objects having an adhesive layer. Therefore, it can be suitable for decoration of lighting covers, decoration of light-transmitting substrates such as window materials or light-transmitting roof materials, display of light-transmitting substrates such as window materials or light-transmitting roof materials, etc.

[0131] [Base sheet]

[0132] The above-mentioned window material may or may not include a base sheet. The base sheet has a function as a support when laminating the adhesive layer on the light-transmitting base layer and a function as a protective layer for the adhesive layer.

[0133] The substrate constituting the substrate sheet is not particularly limited as long as it is a light-transmitting substrate. For example, corona-treated PET, untreated PET, highly transparent PET, annealed PET, UV-cut PET, heat-insulating PET, anti-fog PET, hard-coated PET, sandblasted PET, and other PETs; transparent PI, etc. can be used as the substrate.

[0134] [Method for producing window material]

[0135] The manufacture method of above-mentioned window material is not particularly limited, for example can enumerate after substrate sheet is coated with adhesive composition and made adhesive sheet, the method of bonding adhesive sheet at translucent substrate etc. can also be formed adhesive layer by directly coating adhesive composition at translucent substrate.In this case, preferably with substrate sheet covering the exposed face of the adhesive layer formed on translucent substrate, so that the sticky face that shows adhesive layer can not be exposed indoors or outdoors.In addition, when translucent substrate layer is composed of more than two layers as the second window material 20, the method that adhesive layer is configured between translucent substrate layer etc. can also be enumerated.In this case, as long as after coating adhesive composition on 1 substrate layer and forming adhesive layer, other substrate layers are bonded at the exposed face of adhesive layer.

[0136] Alternatively, the second window material 20 having an adhesive layer between the light-transmitting substrates can be manufactured by preparing two laminates each including a light-transmitting substrate layer and an adhesive layer laminated in contact with each other and bonding the two laminates together with the adhesive layer exposed.

[0137] [use]

[0138] There is no limitation on the scheme in which the above-mentioned window material is used. The scheme in which the above-mentioned window material is used can be appropriately selected according to the purpose. For example, the above-mentioned window material can be applied to buildings such as residences, buildings, warehouses, arcades, vehicles, ships or aircrafts.

[0139] <<Light-transmitting roofing materials>>

[0140] Figure 3 is a cross-sectional view showing an example of a light-transmitting roof material. Figure 3 As shown, in the light-transmitting roofing material 30, a light-transmitting base material layer 31, an adhesive layer 32, and a base sheet 33 are laminated in this order. The adhesive layer 32 is composed of an adhesive composition containing a temperature-sensitive adhesive 32a and polymer microparticles 32b.

[0141] exist Figure 3 In the embodiment, the refractive index of the temperature-sensitive adhesive 32a increases as the temperature decreases, and the increase in the refractive index per 1°C, i.e., the refractive index increase rate, is greater near the melting point than in the temperature range other than the melting point. Therefore, when the temperature of the adhesive layer 32 increases due to sunlight or air temperature, the refractive index difference between the polymer particles 32b and the temperature-sensitive adhesive 32a increases, and the haze value increases. On the other hand, when the temperature of the adhesive layer 32 decreases, the haze value decreases due to the decrease in the refractive index difference between the polymer particles 32b and the temperature-sensitive adhesive 32a. Thus, the turbidity can be changed autonomously according to the temperature, and direct sunlight can be mitigated at high temperatures in summer and sunlight can be taken in at low temperatures in winter.

[0142] Furthermore, it is also possible to design the structure so that the difference in refractive index between the polymer microparticles 32 b and the temperature-sensitive adhesive 32 a decreases as the temperature increases.

[0143] Furthermore, the adhesive force of the adhesive composition constituting the adhesive layer 32 decreases as the temperature decreases, and the amount of adhesive force decrease per 1°C, i.e., the adhesive force decrease rate, is greater near the melting point of the temperature-sensitive adhesive 32a in the adhesive composition than in a temperature range other than the melting point. Therefore, even if air bubbles are drawn in or wrinkles occur when configuring the adhesive layer 32, the adhesive layer 32 can be peeled off and configured again by lowering the temperature of the adhesive layer 32. Thus, the manufacture of the window material can be made easier.

[0144] Regarding the light-transmitting roofing material, the light-transmitting base material layer, adhesive layer, each layer of the base sheet, the manufacturing method and the use thereof are the same as those of the window material.

[0145] <<Adhesive composition>>

[0146] The adhesive composition contains 1 to 100 parts by mass of the polymer fine particles based on 100 parts by mass of the temperature-sensitive adhesive.

[0147] The refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and the increase in the refractive index per 1° C., that is, the refractive index increase rate, is greater near the melting point than in a temperature range other than near the melting point.

[0148] In the case where each refractive index is adjusted in such a way that the refractive index difference between the polymer particles and the thermosensitive adhesive at low temperature becomes smaller, when the temperature of the adhesive layer formed by the adhesive composition rises due to sunlight or air temperature or heating, the refractive index difference between the polymer particles and the thermosensitive adhesive becomes larger, and the haze value becomes higher. On the other hand, when the temperature of the adhesive layer decreases, the refractive index difference between the polymer particles and the thermosensitive adhesive decreases, and the haze value decreases. Conversely, in the case where each refractive index is adjusted in such a way that the refractive index difference between the polymer particles and the thermosensitive adhesive at high temperature becomes smaller, when the temperature of the adhesive layer rises, the haze value decreases, and when the temperature of the adhesive layer decreases, the haze value increases.

[0149] Therefore, in the former case, when an adhesive layer is arranged on a window material or a translucent roof material, the turbidity can be autonomously changed according to the temperature, and direct sunlight can be mitigated in the high temperature of summer and sunlight can be taken in in the low temperature of winter.

[0150] In addition, when an adhesive layer is formed by using an adhesive composition to draw a design such as text, a mark, a pattern, a figure, or a pattern, the design can be made to appear or disappear as the haze caused by a heat source such as lighting or a high temperature caused by sunlight or air temperature appears or disappears. Thus, an object having an adhesive layer can be given excellent display properties (text, mark, or other design) or decorative properties (pattern, figure, or other design).

[0151] In any case, when used as a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, the haze value of the pressure-sensitive adhesive layer becomes lower or higher, thereby enabling visual recognition of the following changes in pressure-sensitive adhesive force even in a scenario where there is no contact thermometer.

[0152] The adhesive force of the adhesive composition decreases as the temperature decreases, and the adhesive force decrease rate per 1°C is greater near the melting point of the temperature-sensitive adhesive in the adhesive composition than in a temperature range other than the melting point.

[0153] Therefore, even when there is air bubble involved or wrinkle etc. when configuring the adhesive layer, by making the temperature of the adhesive layer rise, the adhesive layer can be peeled off and configured again. In addition, the processing components in the manufacturing process can be temporarily fixed firmly, and the processing components can be peeled off without destroying them.

[0154] (Polymer Microparticles)

[0155] The average particle size of the polymer particles is preferably 0.1 μm or more, more preferably 1 μm or more. In addition, the above average particle size is preferably 100 μm or less, more preferably 30 μm or less, and further preferably 10 μm or less. In particular, from the perspective of facilitating the improvement of haze, the above average particle size is further preferably 0.1 μm or more and 10 μm or less, and most preferably 1 μm or more and 6 μm or less. From the perspective of facilitating the transmission of sunlight, the above average particle size is further preferably 6 μm or more and 25 μm or less, and most preferably 6 μm or more and 10 μm or less. From the perspective of facilitating heat insulation, the above average particle size is further preferably 6 μm or more and 25 μm or less, and most preferably 6 μm or more and 10 μm or less.

[0156] In addition, the D90 particle size of the polymer particles is preferably less than the thickness of the adhesive layer, for example, 1 μm to 1000 μm, 3 μm to 100 μm. When the D90 particle size is less than the thickness of the adhesive layer, the surface of the adhesive layer becomes uniform and tends to be less likely to hinder the adhesive force.

[0157] The polymer constituting the polymer microparticles preferably contains a constituent unit derived from a monomer containing one ethylenically unsaturated group. Examples of the ethylenically unsaturated group include (meth)acryloyl, (meth)acrylamide, vinyl and (meth)allyl groups, with (meth)acryloyl and vinyl groups being preferred.

[0158] Examples of the monomer containing one ethylenically unsaturated group include (meth)acrylic acid; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, and hydroxyethyl (meth)acrylate; vinyl monomers such as styrene, vinyl acetate, and acrylonitrile; etc. These may be used alone or in combination of two or more.

[0159] The ratio of the mass of the constituent units derived from the monomer containing one ethylenically unsaturated group to the mass of the polymer constituting the polymer microparticles is preferably 70 mass % or more, more preferably 80 mass % or more, and further preferably 90 mass % or more. The above ratio may be 100 mass %, but is preferably 98 mass % or less.

[0160] The polymer constituting the polymer microparticles may also contain constituent units derived from other monomers copolymerizable with the monomer containing one ethylenically unsaturated group. Examples of other monomers include multifunctional monomers, refractive index adjusting monomers, etc. That is, the polymer constituting the polymer microparticles may also contain constituent units derived from multifunctional monomers or refractive index adjusting monomers.

[0161] The multifunctional monomer can crosslink the multiple molecular chains contained in the polymer constituting the polymer particles. From the viewpoint of the dispersion state of the polymer particles during use or the suppression of deformation and the repeatability of the function, the polymer constituting the polymer particles preferably contains a constituent unit derived from the multifunctional monomer. That is, it is preferred that the polymer particles or the polymer constituting them are crosslinked. The multifunctional monomer has two or more, preferably 2 to 4, double bonds that can be free radically polymerized in the molecule. As multifunctional monomers, for example, bifunctional (meth) acrylates, trifunctional (meth) acrylates, and tetrafunctional (meth) acrylates can be cited. As specific examples, 1,6-hexanediol di(meth) acrylate, 1,9-nonanediol di(meth) acrylate, trimethylolpropane tri(meth) acrylate, pentaerythritol tetra(meth) acrylate, polyethylene glycol 200 di(meth) acrylate, ethoxylated bisphenol A di(meth) acrylate, etc. can be cited. They can be used alone or in combination of two or more. The polyfunctional monomer may be at least one selected from bifunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional (meth)acrylates.

[0162] The ratio of the mass of the constituent units derived from the polyfunctional monomer to the mass of the polymer constituting the polymer microparticles is preferably 0.1 mass % or more, more preferably 1 mass % or more, and preferably 20 mass % or less, more preferably 10 mass % or less.

[0163] The refractive index adjusting monomer may be a monomer having a refractive index of 1.300 to 1.600. Examples of the refractive index adjusting monomer include 2-(o-phenylphenoxy)ethyl acrylate (refractive index: 1.577), 2-(3-phenoxyphenyl)methyl acrylate (refractive index: 1.566), 1-naphthyl acrylate (refractive index: 1.595), acrylamide (refractive index: 1.515), hydroxyacrylamide (refractive index: 1.515), EO-modified bisphenol A diacrylate (refractive index: 1.537), acrylamide (refractive index: 1.515), 2,2,2-trifluoroethyl acrylate (refractive index: 1.348), and methacrylic acid-modified polydimethylsiloxane (refractive index: 1.408). These monomers may be used alone or in combination of two or more.

[0164] The ratio of the mass of the constituent units derived from the refractive index adjusting monomer to the mass of the polymer constituting the polymer microparticles is preferably 0.1 mass % or more, more preferably 1 mass % or more, and preferably 30 mass % or less, more preferably 20 mass % or less, and further preferably 10 mass % or less.

[0165] From the aspect of having a good dispersibility to the thermosensitive adhesive, the polymer microparticles preferably do not contain a constituent unit derived from a reactive emulsifier. A reactive emulsifier refers to an emulsifier having a polymerizable unsaturated bond such as a vinyl group in the molecule. A reactive emulsifier is a polymerizable monomer having an emulsifying function and having a hydrophilic group and a polymerizable group having an unsaturated bond such as a vinyl group in its molecule.

[0166] In the adhesive composition, the content of the polymer particles is 1 part by mass or more and 100 parts by mass or less relative to 100 parts by mass of the temperature-sensitive adhesive. The above content is preferably 5 parts by mass or more, more preferably 20 parts by mass or more. In addition, the above content is preferably 70 parts by mass or less, more preferably 40 parts by mass or less.

[0167] The method for producing polymer microparticles is not particularly limited, and the microparticles can be obtained by conventionally known polymerization methods such as miniemulsion polymerization and suspension polymerization.

[0168] (Thermosensitive adhesive)

[0169] Thermosensitive adhesives have a melting point. Thermosensitive adhesives crystallize at a temperature lower than the melting point, and undergo a phase change and exhibit fluidity at a temperature higher than the melting point. As a result, the adhesive force of the adhesive composition containing the temperature-sensitive adhesive decreases as the temperature decreases, and the amount of decrease in adhesive force per 1°C, i.e., the adhesive force decrease rate, is greater near the melting point of the temperature-sensitive adhesive in the adhesive composition than in a temperature range other than near the melting point.

[0170] The peel strength of the adhesive composition with respect to polyethylene terephthalate (PET) at 23° C. is preferably 0.1 N / 25 mm or less. The lower limit of the peel strength is not particularly limited.

[0171] The adhesive composition preferably has a peel strength of 1.0 N / 25 mm or more with respect to polyethylene terephthalate (PET) at 60° C. The upper limit of the peel strength is not particularly limited.

[0172] The melting point of the temperature-sensitive adhesive is preferably 25° C. or higher, and more preferably 40° C. or higher. In addition, the melting point is preferably 70° C. or lower, and more preferably 60° C. or lower.

[0173] The melting point of the temperature-sensitive adhesive can be adjusted by, for example, changing the composition of the monomer components of the side chain crystalline polymer contained in the temperature-sensitive adhesive. For example, if the length of the side chain in the side chain crystalline polymer is changed, the melting point can be adjusted. When the length of the side chain is long, the melting point of the temperature-sensitive adhesive tends to be high.

[0174] Figure 4Graph showing the change in refractive index of a temperature-sensitive adhesive (melting point 55° C.) produced in the examples described below with respect to temperature changes. Figure 4 As shown, the refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and the increase in the refractive index per 1° C., that is, the refractive index increase rate, is greater near the melting point than in a temperature range other than the melting point.

[0175] The refractive index of the temperature-sensitive adhesive at 23° C. is preferably 0.02 or more higher than the refractive index of the temperature-sensitive adhesive at 60° C. This tends to make it easier to visually recognize changes in white turbidity depending on temperature.

[0176] The temperature-sensitive adhesive preferably includes a side chain crystalline polymer. The side chain crystalline polymer preferably includes a constituent unit of a (meth) acrylic monomer having a straight-chain alkyl group with a carbon number of more than 14. In the constituent unit of a (meth) acrylic monomer having a straight-chain alkyl group with a carbon number of more than 14, the straight-chain alkyl group with a carbon number of more than 14 functions as a side chain crystalline site in the side chain crystalline polymer. That is, the side chain crystalline polymer is, for example, a comb-shaped polymer having a straight-chain alkyl group with a carbon number of more than 14 in the side chain. The side chain is integrated into an orderly arrangement by intermolecular forces, etc., so that the side chain crystalline polymer is crystallized. In addition, the above-mentioned (meth) acrylic monomer refers to an acrylic monomer or a methacrylic monomer. The upper limit of the carbon number of the straight-chain alkyl group is preferably less than 50, more preferably less than 30.

[0177] Examples of the (meth)acrylic acid monomer having a linear alkyl group having 14 or more carbon atoms include hexadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, and behenyl (meth)acrylate. These monomers may be used alone or in combination of two or more.

[0178] The ratio of the mass of the constituent units derived from the (meth)acrylic acid monomer having a linear alkyl group having 14 or more carbon atoms to the mass of the side chain crystalline polymer is preferably 30% by mass or more, more preferably 40% by mass or more. The above ratio is preferably 90% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less.

[0179] The side chain crystalline polymer preferably includes a constituent unit derived from a (meth) acrylic monomer having a linear alkyl group having a carbon number of 1 or more and 12 or less, and a constituent unit derived from a functional group monomer for crosslinking. In addition, the side chain crystalline polymer may also include a constituent unit derived from other monomers that can copolymerize with these monomers. As other monomers, for example, a refractive index adjusting monomer may be cited. That is, the side chain crystalline polymer may also include a constituent unit derived from a refractive index adjusting monomer.

[0180] As the (meth)acrylic acid monomer having a linear alkyl group with a carbon number of 1 to 12, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, etc. can be mentioned. Only one of them can be used, or two or more of them can be used in combination. Among them, methyl (meth)acrylate is preferred because it has high cohesive force and is easy to suppress the decrease in adhesive force when the temperature rises.

[0181] The ratio of the mass of the constituent units derived from the (meth)acrylic acid monomer having a linear alkyl group having 1 to 12 carbon atoms to the mass of the side chain crystalline polymer is preferably 1% by mass or more, more preferably 20% by mass or more, and further preferably 40% by mass or more. The above ratio is preferably 69% by mass or less, and more preferably 60% by mass or less.

[0182] Examples of the functional group monomer include (meth)acrylates having a hydroxyalkyl group such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxyhexyl (meth)acrylate; ethylenically unsaturated monomers having a carboxyl group such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid, and fumaric acid; etc. These may be used alone or in combination of two or more.

[0183] The mass of the constituent units derived from the functional group monomer relative to the mass of the side chain crystalline polymer is preferably 1% by mass or more, more preferably 3% by mass or more. In addition, the above ratio is preferably 20% by mass or less, more preferably 10% by mass or less. When it is 1% by mass or more, there is a trend that the shape retention is good. When it is 20% by mass or less, there is a trend that the viscosity does not excessively become high and the coating property is good.

[0184] The refractive index adjusting monomer may be a monomer having a refractive index of 1.300 to 1.600. Examples of the refractive index adjusting monomer include 2-(o-phenylphenoxy)ethyl acrylate (refractive index: 1.577), 2-(3-phenoxyphenyl)methyl acrylate (refractive index: 1.566), 1-naphthyl acrylate (refractive index: 1.595), acrylamide (refractive index: 1.515), hydroxyacrylamide (refractive index: 1.515), EO-modified bisphenol A diacrylate (refractive index: 1.537), acrylamide (refractive index: 1.515), 2,2,2-trifluoroethyl acrylate (refractive index: 1.348), and methacrylic acid-modified polydimethylsiloxane (refractive index: 1.408). These monomers may be used alone or in combination of two or more.

[0185] The ratio of the mass of the structural unit derived from the refractive index adjusting monomer to the mass of the side chain crystalline polymer is preferably 0.1 mass % or more, more preferably 1 mass % or more, and further preferably 10 mass % or more. The above ratio is preferably 30 mass % or less.

[0186] The weight average molecular weight of the temperature-sensitive adhesive is preferably 200,000 or more, more preferably 400,000 or more. The weight average molecular weight is preferably 2,000,000 or less, more preferably 1,000,000 or less. When it is 200,000 or more, there is a tendency for sufficient adhesive force. When it is 2,000,000 or less, there is a tendency for sufficient coating properties due to reduced viscosity.

[0187] The weight average molecular weight of the temperature-sensitive adhesive can be adjusted by, for example, using a chain transfer agent during polymerization. As the chain transfer agent, for example, mercaptan compounds such as dodecyl mercaptan, mercaptopropionic acid, mercaptosuccinic acid, ethylhexyl mercaptoacetate, mercaptoethanol, and cyclohexanethiol can be cited. These can be used alone or in combination of two or more.

[0188] The refractive index difference between the temperature-sensitive binder and the polymer microparticles at 23°C is preferably less than 0.015, more preferably less than 0.010. The refractive index difference at 60°C is preferably 0.015 or more. The upper limit of the refractive index difference at 60°C is not particularly limited, and is, for example, 0.1.

[0189] The ratio of the mass of the temperature-sensitive adhesive to the mass of the solid content of the adhesive composition is not particularly limited, and is, for example, 50% by mass or more and 95% by mass or less.

[0190] The method for producing the temperature-sensitive adhesive is not particularly limited, and the temperature-sensitive adhesive can be obtained by a conventionally known polymerization method such as solution polymerization and UV polymerization.

[0191] The adhesive composition may also contain a crosslinking agent for crosslinking the temperature-sensitive adhesive. That is, the temperature-sensitive adhesive may be crosslinked. Examples of the crosslinking agent include aziridine-based crosslinking agents, metal chelate-based crosslinking agents, epoxy-based crosslinking agents, and isocyanate-based crosslinking agents.

[0192] In the adhesive composition, the content of the crosslinking agent is not particularly limited, for example, relative to 100 parts by mass of the temperature-sensitive adhesive, it is 0.1 parts by mass or more and 10 parts by mass or less. When it is 0.1 parts by mass or more, there is a tendency that the shape retention is not easy to become low. In addition, when it is 10 parts by mass or less, there is a tendency that it is easy to exert high adhesive force.

[0193] The adhesive composition may contain other additives such as organic solvents, inhibitors for inhibiting the progress of crosslinking, tackifying resins (tackifiers), ultraviolet (UV) absorbers, light stabilizers (HALS), antioxidants, infrared absorbers, dyes, pigments, etc.

[0194] <<Adhesive Sheet>>

[0195] The pressure-sensitive adhesive sheet includes a pressure-sensitive adhesive layer comprising a pressure-sensitive adhesive composition.

[0196] As described above, the temperature-sensitive light-adjusting liquid stack of Patent Document 1 requires a dedicated structure for maintaining the shape of the temperature-sensitive light-adjusting liquid. Therefore, when installing it in an already installed window or roof, a large-scale project such as replacing the window together is required, which makes it difficult to introduce.

[0197] In contrast, a pressure-sensitive adhesive sheet has the following advantages: it does not require a dedicated structure for maintaining its shape, can be easily installed by simply sticking it to an already installed window or roof, and can easily be given a function of autonomously changing the white turbidity according to the temperature.

[0198] The thickness of the adhesive layer is not particularly limited, but is preferably 5 μm or more and 1 mm or less, and more preferably 10 μm or more and 100 μm or less. In addition, the thicker the adhesive layer, the more likely it is that a dimming function will be exhibited by adding a small amount of polymer particles. The thinner the thickness, the more likely it is that a large amount of polymer particles need to be added to exhibit the dimming function.

[0199] The difference between the haze value of the adhesive layer at 23° C. and the haze value at 60° C. is preferably 10% or more. In particular, the haze value of the adhesive layer at 60° C. is more preferably 10% or more higher than the haze value at 23° C. This tends to make it easier to visually recognize the change in white turbidity due to temperature.

[0200] The haze value of the adhesive layer at 23°C is preferably 20% or less, more preferably 10% or less. The lower limit of the haze value at 23°C is not particularly limited. In addition, the haze value of the adhesive layer at 60°C is preferably 12% or more, more preferably 20% or more. The upper limit of the haze value at 60°C is not particularly limited, for example, 70% or less, 50% or less.

[0201] The difference between the solar transmittance at 23°C and the solar transmittance at 60°C of the adhesive layer is preferably 10% or more. The solar transmittance at 60°C of the adhesive layer is preferably 10% or more lower than the solar transmittance at 23°C. In addition, in this specification, the solar transmittance of the adhesive layer is a value measured by the method described in the Examples described later.

[0202] The solar transmittance of the adhesive layer at 23°C is preferably 30% or more, more preferably 40% or more. The upper limit of the solar transmittance at 23°C is not particularly limited, and is, for example, 95% or less or 85% or less. In addition, the solar transmittance of the adhesive layer at 60°C is preferably 60% or less, more preferably 40% or less, and further preferably 30% or less. The lower limit of the solar transmittance at 60°C is not particularly limited, and is, for example, 5% or more or 15% or more.

[0203] The adhesive sheet may also include a substrate sheet. The substrate constituting the substrate sheet is not particularly limited as long as it is a light-transmitting substrate. As the substrate, for example, corona-treated PET, untreated PET, highly transparent PET, annealed PET, UV-cut PET, heat-insulating PET, anti-fog PET, hard-coated PET, sandblasted PET, and other PETs; transparent PI, etc. can be used.

[0204] The adhesive layer may be formed on only one side of the substrate sheet or on both sides. Alternatively, an adhesive layer may be formed on one side of the substrate sheet and an adhesive layer not meeting the above description may be formed on the other side.

[0205] Similar to the substrate sheet, a release sheet may be laminated on the surface of the adhesive layer.

[0206] The adhesive sheet can be produced using the above-mentioned adhesive composition by a common method. For example, a coating solution prepared by adding a solvent or a crosslinking agent to the adhesive composition as needed is applied to a substrate sheet by a coater, and then dried by heating or the like to form an adhesive layer.

[0207] As the coater, for example, a knife coater, a roll coater, a calendar coater, a comma coater, etc. can be mentioned. In addition, depending on the coating thickness or the viscosity of the coating liquid, a gravure coater, a rod coater, etc. can also be mentioned.

[0208] <<Processing method of workpiece>>

[0209] The adhesive force of the above-mentioned adhesive sheet decreases as the temperature decreases, and the adhesive force reduction rate is greater near the melting point of the thermosensitive adhesive than in the temperature range outside the melting point. Therefore, by adjusting the temperature, the workpiece in the manufacturing process can be firmly temporarily fixed and can be peeled off without destroying the workpiece. Moreover, the refractive index of the thermosensitive adhesive increases as the temperature decreases, and the refractive index rise rate is greater near the melting point than in the temperature range outside the melting point. Therefore, the haze value of the adhesive layer becomes lower or higher, and even in the case of no contact thermometer, the change of the adhesive force can be visually identified (for example, when each refractive index is adjusted in a manner that the refractive index difference between the polymer particles and the thermosensitive adhesive at high temperature becomes larger, white turbidity occurs through the adhesive layer, and the appearance of the adhesive force can be visually identified. When each refractive index is adjusted in a manner that the refractive index becomes smaller, white turbidity does not occur through the adhesive layer, and the appearance of the adhesive force can be visually identified). Therefore, the above-mentioned adhesive sheet can be suitable for the following (1) or (2) processing method of the workpiece.

[0210] (1) A method for processing a workpiece, comprising: (a) bringing the workpiece into contact with the adhesive layer of the adhesive sheet; (b) confirming that the adhesive layer exhibits adhesive strength by confirming that the adhesive layer is turbid or not turbid; (c) processing the workpiece fixed to the adhesive layer by the adhesive strength exhibited by the adhesive layer; (d) confirming that the adhesive layer does not exhibit adhesive strength by confirming that the adhesive layer is not turbid or is turbid; and (e) removing the processed workpiece from the adhesive layer that does not exhibit adhesive strength.

[0211] (2) A method for processing a workpiece, comprising: (a') bringing a support body and the workpiece into contact, or bringing the workpieces into contact with each other via the adhesive layer possessed by the adhesive sheet; (b') confirming that the adhesive layer exhibits adhesive strength by confirming that the adhesive layer has become cloudy or has not become cloudy; (c') processing the workpiece that is fixed to the support body via the adhesive layer due to the adhesive strength exhibited by the adhesive layer, or at least one of the plurality of workpieces that are fixed via the adhesive layer; (d') confirming that the adhesive layer does not exhibit adhesive strength by confirming that the adhesive layer has not become cloudy or has become cloudy; and (e') removing the processed workpiece from the adhesive layer that has not exhibited adhesive strength.

[0212] In (a), for example, an adhesive sheet having an adhesive layer and a substrate sheet laminated on one side of the adhesive layer is used, and the temperature is set to be above the melting point of the temperature-sensitive adhesive, and the adhesive layer is attached to the object to be processed. In addition, in (a'), for example, an adhesive sheet having an adhesive layer and a release sheet laminated on one side of the adhesive layer, or an adhesive sheet having a substrate sheet and an adhesive layer laminated on both sides of the substrate sheet and a release sheet laminated in one of the adhesive layers is used, and the temperature is set to be above the melting point of the temperature-sensitive adhesive, and the adhesive layer is attached to a support (pedestal, etc.) or the object to be processed. Afterwards, the release sheet is peeled off, and another adhesive layer is attached to another support or the object to be processed. In order to set the adhesive sheet to a temperature above the melting point of the temperature-sensitive adhesive, for example, a heating unit such as a heater can be used.

[0213] As described above, in the above-mentioned adhesive sheet, the haze value of the adhesive layer decreases or increases depending on the temperature, so even in a scenario where there is no contact thermometer, the change in adhesive strength can be visually recognized. Therefore, in (b) and (b'), by confirming that the adhesive layer is turbid or not turbid, it can be confirmed that the adhesive layer exhibits adhesive strength and that the workpiece is temporarily fixed.

[0214] In (c) and (c'), the processing method is not particularly limited, and examples thereof include grinding, dicing, die bonding, wire bonding, etching, vapor deposition, molding, circuit formation, inspection, product inspection, cleaning, transfer, arrangement, repair, and device surface protection.

[0215] In (d) and (d'), the adhesive sheet is set to a temperature lower than the melting point of the temperature-sensitive adhesive. Then, by confirming that the adhesive layer is not turbid or is turbid, it can be confirmed that the adhesive layer does not show adhesive force and that the workpiece can be peeled off. In order to set the adhesive sheet to a temperature lower than the melting point of the temperature-sensitive adhesive, for example, a cooling unit such as a fan can be used.

[0216] In (e) and (e'), since the adhesive layer does not show adhesive force, the workpiece can be easily peeled off.

[0217] The workpiece is not particularly limited as long as it is an article that needs to be temporarily fixed during processing, and examples thereof include electronic components such as ceramic capacitors, semiconductor chips, and LED chips, and thin film components such as thin film touch sensors.

[0218] Example

[0219] Hereinafter, the present invention will be described in more detail with reference to Examples, but the scope of the present invention is not limited to these Examples.

[0220] Hereinafter, various chemicals used in the examples will be collectively described.

[0221] VA: BLEMMER VA (behenyl acrylate) manufactured by NOF Corporation

[0222] MMA: Methyl methacrylate manufactured by Tokyo Chemical Industry Co., Ltd.

[0223] St: Styrene manufactured by Tokyo Chemical Industry Co., Ltd.

[0224] A-HD-N: A-HD-N (1,6-hexanediol diacrylate) manufactured by Shin-Nakamura Chemical Industry Co., Ltd.

[0225] C1A: Methyl acrylate manufactured by Nippon Shokubai Co., Ltd.

[0226] AA: Acrylic acid manufactured by Nippon Shokubai Co., Ltd.

[0227] NF-13: HITENOL NF-13 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.

[0228] PEROYL L: PEROYL L (dilauroyl peroxide) manufactured by NOF Corporation

[0229] PERBUTYL ND: PERBUTYL ND (tert-butyl peroxyneodecanoate) manufactured by NOF Corporation

[0230] PERHEXYL PV: PERHEXYL PV (tert-hexyl peroxypivalate) manufactured by NOF Corporation

[0231] PZ33: CHEMITITE PZ33 (aziridine-based crosslinking agent) manufactured by Nippon Shokubai Co., Ltd.

[0232] [Production of polymer microparticles]

[0233] The monofunctional monomer, the multifunctional monomer and the initiator are added to the reaction container in the proportions shown in Table 1. The mixture in the reaction container is stirred with a scraper to make it uniformly mixed. Then, an aqueous medium and an emulsifier in the proportions shown in Table 1 are added to the reaction container to obtain a mixed solution. Water is used as the aqueous medium. The aqueous medium is added in such a way that the ratio of the mass of the monofunctional monomer in the mixed solution to the total mass of the monofunctional monomer and the mass of the aqueous medium is 40% by mass. Furthermore, the mixed solution is stirred at 7500 rpm for 5 minutes using a homogenizer manufactured by IKA (main body: T 25digital ULTRA-TURRAX, shaft generator: S25N-25F) to make the monomer components granular. Finally, nitrogen is introduced into the mixed solution for bubbling, and after removing the air (oxygen) in the mixed solution, it is heated and stirred at 67°C for 2 hours and at 80°C for 2 hours to polymerize the monomer components. Then, the aqueous medium was removed from the produced fine particles by suction filtration and vacuum drying, thereby obtaining polymer fine particles 1 to 3.

[0234] Polymer microparticles 4 were obtained in the same manner as in the method for producing polymer microparticles 3, except that the mixed solution was stirred at 2800 rpm for 5 minutes using a homogenizer.

[0235] Polymer microparticles 5 were obtained in the same manner as in the method for producing polymer microparticles 3, except that the mixed solution was stirred at 2800 rpm for 2 minutes using a homogenizer.

[0236] (Average particle size of polymer microparticles)

[0237] The particle size distribution of the polymer microparticles was measured using a laser diffraction particle size distribution meter "Mastersizer 3000" manufactured by Malvern. In the particle size distribution, the particle size corresponding to 50% of the cumulative volume frequency calculated from the smaller particle size of the polymer microparticles was defined as the "average particle size". The results are shown in Table 1.

[0238] [Table 1]

[0239]

[0240] [Manufacture of temperature-sensitive adhesive]

[0241] The monomers were added to the reaction container in the proportions shown in Table 2. The solvent (ethyl acetate / heptane = 70 / 30 (mass ratio) was added to the reaction container to dilute the monomers in such a manner that the monomer concentration became 30 mass %. Then, nitrogen was introduced into the monomer dilution for bubbling while the monomer dilution was stirred and heated. At the time point when the liquid temperature reached 55°C, an initiator was added to the monomer dilution in the proportions shown in Table 2. Furthermore, after heating and stirring the liquid in the reaction container at 55°C for 4 hours, the temperature of the oil bath was increased to 80°C. At the time point when the liquid temperature exceeded 70°C, an accelerator was added to the reaction solution in the proportions shown in Table 2. Finally, the mixture was heated and stirred at 80°C for 2 hours to obtain a temperature-sensitive adhesive.

[0242] (Weight average molecular weight of temperature sensitive adhesive)

[0243] The results are shown in Table 2.

[0244] (Melting point of temperature-sensitive adhesive)

[0245] The melting point of the temperature-sensitive adhesive was measured from the temperature of the endothermic peak top when measuring in the range of -30 to 100° C. at a scanning rate of 10° C. / min using a DSC (differential scanning calorimeter) manufactured by Seiko Instruments.

[0246] [Table 2]

[0247]

[0248] [Manufacturing of adhesive sheet]

[0249] The obtained polymer particles were added to a solvent (heptane) and stirred with a spatula to obtain a dispersion. The dispersion was added to the obtained temperature-sensitive adhesive. The polymer particles and the temperature-sensitive adhesive were added in the ratios shown in Tables 3 and 4, and the solvent was added in a ratio to give a solid content concentration of 25% by mass.

[0250] To the adhesive composition, an inhibitor was added in the ratio shown in Table 3 and Table 4, and after uniform stirring with a spatula, a crosslinking agent was added in the ratio shown in Table 3 and Table 4. The adhesive composition was applied to the corona-treated surface of a PET film (thickness 100 μm) using a bar coater. Thereafter, the PET film was heated and dried at 110° C. for 3 minutes in a hot air circulation oven to obtain an adhesive sheet (Examples 1 to 5) having an adhesive layer (thickness 40 μm) including the crosslinked adhesive composition.

[0251] (Refractive index of polymer microparticles and temperature-sensitive adhesive)

[0252] The refractive index of the obtained polymer microparticles and the temperature-sensitive adhesive at 23° C. and 60° C. was measured using an automatic refractometer “Abbemat 350” manufactured by Anton Paar. The results are shown in Tables 3 and 4.

[0253] (Haze value of adhesive layer)

[0254] The adhesive layer of the obtained adhesive sheet was measured for haze values ​​at 23°C and 60°C using a spectrophotometer "CM3600" (light source C) manufactured by Konica Minolta (Co., Ltd.) in accordance with ASTM D1003. The adhesive sheet was bonded to the ITO glass surface for measurement using ITO glass as a reference. The results are shown in Tables 3 and 4.

[0255] (Peel Strength)

[0256] For the obtained adhesive sheet, the 180° peel strength relative to polyethylene terephthalate (PET) at 23°C and 60°C was measured in accordance with JIS Z0237. Specifically, the adhesive sheet was attached to PET and left to stand for 20 minutes, and then 180° peeling was performed at a speed of 300 mm / min using a load cell. PET used a film-like and untreated film with a thickness of 25 μm. The bonding of the adhesive sheet to PET was performed by reciprocating a 2 kg roller 5 times on the adhesive sheet. The results are shown in Tables 3 and 4.

[0257] In addition, the peel strength of the adhesive sheet was also measured at temperatures between 23°C and 60°C, and the change in the adhesive strength reduction rate, which is the amount of adhesive strength reduction per 1°C of the adhesive sheet, was confirmed. As a result, it was confirmed that the adhesive strength reduction rate near 55°C, the melting point of the temperature-sensitive adhesive, was greater than that in temperature ranges other than the melting point of the temperature-sensitive adhesive.

[0258] (Solar transmittance)

[0259] For the obtained adhesive sheet, the solar transmittance at 23°C and 60°C was measured using a spectrophotometer "V770DS" manufactured by JASCO Corporation in accordance with 6.5 of JIS A5759:2016. However, in order to heat to 60°C for measurement, an ITO glass with a thickness of 1.1 mm ("GMT-100-12" manufactured by GEOMATEC) was used as the object to which the adhesive sheet was attached. Specifically, a test piece was prepared by attaching the adhesive sheet to a single surface of the ITO glass. At 23°C and 60°C (the surface temperature of the ITO glass measured by a contact thermometer), the glass surface of the test piece was directed toward the light source, and the spectral transmittance of each wavelength of 300 to 2500 nm was measured using a spectrophotometer. As specified in JIS A5759:2016, the solar transmittance was calculated based on the relative spectral distribution of sunlight. The results are shown in Tables 3 and 4.

[0260] (Thermal insulation)

[0261] For the obtained adhesive sheet, Figure 5 to Figure 7 The thermal insulation was evaluated as shown. Specifically, an adhesive sheet 1 was attached to a glass plate 2 to prepare a test piece. The test piece was placed as the top surface on a wooden frame 4 with a width of 120 mm, a depth of 200 mm, and a height of 100 mm in a manner that the adhesive sheet surface was facing upward. A thermometer (thermocouple) 3 was set at a position 10 mm below the glass surface. As a windshield, the side and bottom of the wooden frame 4 were covered with a polyethylene sheet. The wooden frame 4 on which the test piece was placed was set on a metal frame 5 at a height of 1000 mm from the ground 6. The temperature rise value of the thermocouple 3 during sunlight exposure (sun exposure time: about 360 minutes, average temperature: 32°C) was recorded. The temperature rise value was recorded in the same way as the test piece of the glass plate to which the adhesive sheet was not attached as a blank. The difference in temperature rise value with the blank was calculated. The results are shown in Tables 3 and 4.

[0262] [Table 3]

[0263]

[0264] As is clear from Table 3, according to Examples 1 and 2, the adhesive layers of Examples 1 and 2 having the aforementioned prescribed configurations can autonomously change the white turbidity according to the temperature. In addition, it can be seen that the adhesive force decreases by lowering the temperature. Therefore, it can be seen from Examples 1 and 2 that the window material or the light-transmitting roof material having the above-mentioned adhesive layer can autonomously change the white turbidity according to the temperature, and the adhesive layer can be peeled off and reconfigured, so the manufacturing is easy.

[0265] [Table 4]

[0266]

[0267] Description of Reference Numerals

[0268] 10First Window Material

[0269] 11 light-transmitting substrate layer

[0270] 12 adhesive layer

[0271] 12a Temperature sensitive adhesive

[0272] 12b Polymer particles

[0273] 13 substrate sheet

[0274] 20 Second window material

[0275] 21a, 21b light-transmitting base material layer

[0276] 22 adhesive layer

[0277] 22a Temperature sensitive adhesive

[0278] 22b Polymer microparticles

[0279] 30Translucent roofing materials

[0280] 31 light-transmitting substrate layer

[0281] 32 adhesive layers

[0282] 32a Temperature sensitive adhesive

[0283] 32b Polymer microparticles

[0284] 33 substrate sheets.

Claims

1. A window material, characterized in that: It comprises at least one light-transmitting substrate layer and at least one adhesive layer, The adhesive layer includes an adhesive composition containing 1 to 100 parts by mass of polymer microparticles relative to 100 parts by mass of the temperature-sensitive adhesive. The refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and The increase in refractive index per 1°C, that is, the rate of increase in refractive index of the temperature-sensitive adhesive, is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive. The adhesive force of the adhesive composition decreases as the temperature decreases, and The amount of decrease in adhesive strength per 1° C., that is, the adhesive strength reduction rate of the adhesive composition is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

2. The window material according to claim 1, wherein The temperature-sensitive adhesive comprises a side-chain crystalline polymer, The side chain crystalline polymer contains 30 to 90% by mass of a structural unit derived from a (meth)acrylic acid monomer having a linear alkyl group having 14 or more carbon atoms.

3. The window material according to claim 1, wherein A difference between a haze value of the adhesive layer at 60° C. and a haze value of the adhesive layer at 23° C. is 10% or more.

4. A light-transmitting roof material, characterized in that: It comprises at least one light-transmitting substrate layer and at least one adhesive layer, The adhesive layer includes an adhesive composition containing 1 to 100 parts by mass of polymer microparticles relative to 100 parts by mass of the temperature-sensitive adhesive. The refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and The increase in refractive index per 1°C, that is, the rate of increase in refractive index of the temperature-sensitive adhesive, is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive. The adhesive force of the adhesive composition decreases as the temperature decreases, and The amount of decrease in adhesive strength per 1° C., that is, the adhesive strength reduction rate of the adhesive composition is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

5. The light-transmitting roofing material according to claim 4, wherein: The temperature-sensitive adhesive comprises a side-chain crystalline polymer, The side chain crystalline polymer contains 30 to 90% by mass of a structural unit derived from a (meth)acrylic acid monomer having a linear alkyl group having 14 or more carbon atoms.

6. The light-transmitting roofing material according to claim 4, wherein: A difference between a haze value of the adhesive layer at 60° C. and a haze value of the adhesive layer at 23° C. is 10% or more.

7. A building, characterized in that: A window material according to any one of claims 1 to 3 and / or a light-transmitting roof material according to any one of claims 4 to 6.

8. A vehicle, a vessel or an aircraft, characterized in that: A window material according to any one of claims 1 to 3 and / or a light-transmitting roof material according to any one of claims 4 to 6.

9. An adhesive composition comprising 1 to 100 parts by mass of polymer microparticles per 100 parts by mass of a temperature-sensitive adhesive, wherein: The refractive index of the temperature-sensitive adhesive increases as the temperature decreases, and The increase in refractive index per 1°C, that is, the rate of increase in refractive index of the temperature-sensitive adhesive, is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive. The adhesive force of the adhesive composition decreases as the temperature decreases, and The amount of decrease in adhesive strength per 1° C., that is, the adhesive strength reduction rate of the adhesive composition is greater near the melting point of the temperature-sensitive adhesive than in a temperature range other than near the melting point of the temperature-sensitive adhesive.

10. The adhesive composition according to claim 9, wherein The adhesive force is 1 N / 25 mm or more at 60°C and 0.1 N / mm or less at 23°C.

11. The adhesive composition according to claim 9, wherein The temperature-sensitive adhesive comprises a side-chain crystalline polymer, The side chain crystalline polymer contains 30 to 90% by mass of a structural unit derived from a (meth)acrylic acid monomer having a linear alkyl group having 14 or more carbon atoms.

12. An adhesive sheet, characterized in that: A pressure-sensitive adhesive layer comprising the pressure-sensitive adhesive composition according to any one of claims 9 to 11 is provided.

13. The adhesive sheet according to claim 12, wherein A difference between a haze value of the adhesive layer at 60° C. and a haze value of the adhesive layer at 23° C. is 10% or more.

14. A method for processing a workpiece, characterized in that: Include: Bringing a workpiece into contact with the adhesive layer of the adhesive sheet according to claim 12; Confirming that the adhesive layer exhibits adhesive strength by confirming that the adhesive layer is cloudy or not cloudy; processing the workpiece fixed to the adhesive layer by the adhesive force exerted by the adhesive layer; Confirming that the adhesive layer does not show adhesive force by confirming that the adhesive layer is not cloudy or is cloudy; as well as The processed object is removed from the adhesive layer which does not exhibit adhesive force.

15. A method for processing a workpiece, characterized in that: Include: Bringing a support body and a workpiece, or bringing the workpieces into contact with each other via the adhesive layer of the adhesive sheet according to claim 12; Confirming that the adhesive layer exhibits adhesive strength by confirming that the adhesive layer is cloudy or not cloudy; Processing the object fixed to the support through the adhesive layer by the adhesive force of the adhesive layer, or at least one of the plurality of objects fixed through the adhesive layer; Confirming that the adhesive layer does not show adhesive force by confirming that the adhesive layer is not cloudy or is cloudy; as well as The processed object is removed from the adhesive layer which does not exhibit adhesive force.